Pemberian Sari Kacang Hijau Untuk Meningkatkan Kadar Hemoglobin Ibu Hamil Dengan Anemia Ringan - Indah Purwati; Surtiningsih Surtiningsih; Linda Yanti (Medika: Jurnal Ilmiah Kesehatan, 2023)
Anemia is a condition of reduced red blood cells or commonly referred to as erythrocytes in blood circulation or hemoglobin so that they are unable to fulfill their function as oxygen carriers to all tissues (Astuti & Ertiana, 2018). Anemia can indirectly cause complications such as abortion (1.6%), premature labor (10%), infection (5.5%), causing his disorder (4%), the first stage lasts a long time (1.8%), the second stage lasts a long time (4.9%), postpartum hemorrhage (30.1%), low birth weight (62%), (Kemenkes RI, 2017). In addition to standard care, there is also care that can be given as an additional effort to increase hemoglobin levels in pregnant women, namely by consuming Ambon banana, spinach juice, honey, chicken liver, guava juice and green bean juice. According to the results of research by Dewi, et al (2017), consuming mung bean juice 2x/250ml for 14 days is very effective in increasing hemoglobin levels in pregnant women with anemia. Case Presentation: Mrs. E, 23 years old, G1P0A0Ah0, 35 weeks and 3 days of gestation, came to the health center wanting to check her condition with the main complaint recently feeling dizzy, weak and easily tired when doing daily activities. On general examination, it was found that BP: 100/60 mmHg, N: 82 x/minute, S: 36.5, R: 22 x/minute. Special examination found that the eyes and conjunctiva were slightly pale, the rest were within normal limits. In the supporting examination, the result of Hb was less than the normal limit of 10.2g/dl. Conclusion: After midwifery care was performed by providing complementary care of green bean extract 2x/250ml for 7 days, Mrs E's Hb increased from 10.2g/dl to 11.1 g/dl, eyes and conjunctiva were no longer pale.